2020
DOI: 10.47338/jns.v10.704
|View full text |Cite
|
Sign up to set email alerts
|

Phytobezoar causing intestinal obstruction in a neonate: A case report

Abstract: Background: Phytobezoars are concretions of non-digestible vegetative matter in the gastroin­testinal tract and are a rare cause of intestinal obstruction in children. Case presentation: We report a case of intestinal obstruction in a 2-day-old neonate with no specific radiological features pointing to any common etiology. On exploratory laparotomy, a swollen raisin was found impacted in the ileum causing intestinal obstruction. The history taken in retrospect revealed that the elder sibling had witnessed her … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Lactobezoars are milk curds that appear in low birth weight neonates who are fed a highly concentrated formula within the first week of life [ 7 ]. Soluble and undigested fibers are far more common in adults and are rarely reported in childrens [ 8 ]. The most common clinical symptoms are abdominal pain (49–100%), epigastric discomfort (80%), nausea, and vomiting (35–75%) [ 8 ], so, our patient has similar signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobezoars are milk curds that appear in low birth weight neonates who are fed a highly concentrated formula within the first week of life [ 7 ]. Soluble and undigested fibers are far more common in adults and are rarely reported in childrens [ 8 ]. The most common clinical symptoms are abdominal pain (49–100%), epigastric discomfort (80%), nausea, and vomiting (35–75%) [ 8 ], so, our patient has similar signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble and undigested fibers are far more common in adults and are rarely reported in childrens [ 8 ]. The most common clinical symptoms are abdominal pain (49–100%), epigastric discomfort (80%), nausea, and vomiting (35–75%) [ 8 ], so, our patient has similar signs and symptoms. Intestinal phytobezoars are diagnosed by radiological imaging approaches such as routine abdomen radiography in an upright posture, abdominal ultrasound, and abdominal computed tomography [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patcharu et al reported a case of radiolucent raisin obstruction of small bowel in 2 days old neonate. 44 They remove it by enterotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Swollen crystal gel was removed by enterotomy but patient succumbed due to anastomotic leak. Patcharu et al 42 reported a case of radiolucent raisin obstruction of small bowel in 2 days old neonate removed byenterotomy.…”
Section: Reported Spontaneousmentioning
confidence: 99%